Modified Graham’s Patch Repair Versus Graham’s Patch Repair for Treatment of Perforated Peptic Ulcer in Terms of Postoperative Morbidity / Mortality - Khan, Fatima Kamran; Shah, Mahin; Sheikh, Irfan Ali; Mahmood, Khalid; Hassan, Neelofur (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the surgical procedures; graham’s patch repair and modified graham’s patch repair for the treatment of perforated peptic ulcer in terms of their post-operative morbidity and mortality. Study Design: Comparative cross-sectional study. Place and duration of study: Combined Military Hospital Rawalpindi, from May 2020 to Apr 2021. Methodology: We conducted the study on 60 subjects divided into groups of two, (Group A and Group B) selected via convenience sampling. Group A underwent Graham’s repair and Group B underwent modified Graham’s repair. The morbidity and mortality of both the groups was compared statistically with data analysis done using SPSS-23. Results: The average operating time and hospital stay was 84.93 ± 7.06 minutes and 7.3 ± 1.63 days for group A and 96.9 ± 9.67 minutes and 7.56 ± 2.27 days for group B, respectively. For both groups, there was no significant association to any complications (p>0.05). Conclusion: Graham’s repair and modified Graham’s repair are equally effective leaving the decision to the surgeon’s preference. We however recommend using Graham’s repair in unstable patients.